Study of current status of bacteriological prevalence and profile in an inborn unit of SNCU in central India - Agrawal, Avyact; Awasthi, Sukarn; Ghanghoriya, Pawan; Singh, Shivraj (International Journal of Contemporary Pediatrics, 2018)
Background: About 43% of the under-five child mortality is contributed by neonatal death. According to National Neonatal Perinatal Database (NNPD) in inborn births, Klebsiella pneumonia was the most commonly associated pathogen, followed by Staphylococcus aureus. Hence to know the prevalence and profile of bacterial infection in the inborn unit of an SNCU in Central India,this study was done. Methods: This is a cross sectional study done in the Inborn Unit of SNCU, Department of Paediatrics, Netaji Subhash Chandra Bose Medical College and Hospital, Jabalpur (M.P.), INDIA done between 1st March 2015 to 31st August 2016 where the blood sample and data collection of the suspected patients was done. Samples were then sent for culture and sensitivity testing. All the details then entered in Microsoft Excel Sheet and data was analysed using SPSS v 20. Results: The prevalence of bacteriologically positive sepsis was found to be 5.06% (in 43patients out of 850 examined cases). It was more prevalent among males that is in 24 among total 43 culture positives (55.8%), low birth weight were 37 (86% of culture positive patients)and preterm were 35(81.4% of culture positive patients). The most common pathogen associated was found to be Klebsiella pneumonia which was detected in 16 patients (37.2% of all bacteriologically positive patients) followed by E. coli and Pseudomonas, each in 7 patients (16.28%). Conclusions: Though we are on the track of minimising morbidities still we have a high prevalence of neonatal sepsis in inborn unit so sepsis related morbidities can be prevented if timely interventions are done.